Clinical significance of CYP11B2 immunostaining in unilateral primary aldosteronism - Viukari, Marianna (Bioscientifica Ltd, 2025)
Objective: The associations between adrenal histopathology, lateralization studies, and surgical outcomes in primary aldosteronism remain poorly characterized. We examined the value of immunohistochemical analysis of CYP11B2 for evaluation of adrenalectomy outcomes after anatomical versus functional subtyping.
Design: A retrospective multicenter study of 277 patients operated for primary aldosteronism who had an adrenalectomy sample available in the Finnish biobanks from 1 January 2000 to 31 December 2019. Adrenal slides from biobanks were analyzed centrally after CYP11B2 and CYP11B1 staining. Clinical data were obtained from patient registries. Histopathological diagnosis and cure after surgery were assessed as outcome measures.
Results: Re-evaluation with CYP11B2 staining changed the histopathological diagnosis in 91 patients (33%). The presence of a CYP11B2-positive adenoma and the use of functional subtyping independently predicted clinical cure of primary aldosteronism. CYP11B2-positive <7 mm nodules were more frequent in patients without clinical cure, whereas CYP11B2-positive micronodules were common in all patients and had no impact on adrenalectomy outcomes. Small CYP11B2-positive nodules and micronodules were equally prevalent regardless of the subtyping method applied. Clinical cure rates were lower and CYP11B2-negative adenomas more common after adrenalectomy based on anatomical imaging than functional studies.
Conclusions: Incorporating CYP11B2 staining in histopathological diagnosis enhances the prediction of surgical outcomes in primary aldosteronism. A finding of CYP11B2-positive adenoma is indicative of cure of primary aldosteronism, whereas smaller CYP11B2-positive nodules associate with poorer results at postoperative evaluation. Functional subtyping methods decrease the operations of CYP11B2-negative adenomas and are superior to anatomical imaging in identifying unilateral primary aldosteronism.